Impact of species diversity, stand age and environmental factors on leaf litter decomposition in subtropical forests in China - Trogisch, S; He, J; Hector, A; Scherer-Lorenzen, M (Springer Verlag, 2016)
Background and aims Tree diversity is considered to influence decomposition either by changing environmental conditions or by non-additive litter mixture effects. Thus, we examined the influence of tree species richness, forest age and environmental factors on single-species decomposition, and tested the hypothesis that high litter species diversity induces predominantly positive non-additive mixture effects on decomposition processes. Methods Decomposition trials using litter bags were performed in subtropical forests in China. Plot-specific decompositions rates of the abundant species Schima superba were related to environmental factors across 27 forest stands differing in age and tree species richness. Effects of litter species diversity on decomposition and N loss was assessed based on 27 plot-specific litter mixtures comprising 7 to 17 species. Results Decomposition rate of Schima superba leaf litter was mainly affected by stand characteristics and microclimate but not tree diversity. Two thirds of plot-specific litter mixtures showed a positive non-additive mixture effect whose strength was marginally positively influenced by litter species richness. Conclusions Tree diversity at stand level does not directly influence decomposition of a common litter substrate. However, our results suggest that tree species richness in the litter layer can indirectly promote decomposition and nutrient cycling via positive non-additive mixture effects.